EVALUATION OF ANTI-DIARRHOEAL ACTIVITY OF AMARANTHUS TRICOLOR LINN IN EXPERIMENTAL ANIMALS - Alam, Samsul (Innoriginal: International Journal of Sciences, 2015)
Objective: To evaluate the anti-diarrhoeal activity of different extracts of the leaves ofAmaranthus tricolor Linn. using different animal models. Methods: The shade dried leaves ofAmaranthus tricolor.L was extracted with ethanol (95%) and then partitioned by petroleum ether, chloroform and ethyl acetate. The anti-diarrhoeal activity of various extracts ofAmaranthus tricolor was evaluated using castor oil induced diarrheal model in rats, castor oil-induced enter pooling in rats and gastrointestinal motility test in rats. Results: The results revealed that the ethanolic extract and ethyl acetate fractions significantly inhibited diarrhea and reduced the distance travelled by the activated charcoal in intestine in rats. Conclusion: Our results showed that Amaranthus tricolor displayed potent anti-diarrhoeal properties, supporting the ethno-medical use given to this plant for treatment of diseases.